The 4E‘s Model of Enactivism through Improvisation within DMIs - Corintha, Isabela; Cabral, Giordano (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação Musical, 2021)
This paper describes how a theoretical framework focused on the 4E‘s model which describe the mind as fundamentally: embodied, embedded, extended and enactive, within the paradigm of enactive music cognition can contribute to the design of Digital Music Instruments (DMIs). From an epistemological perspective, we discuss improvisation within the Western academic music culture through two examples of DMIs created to improvise in a MIDI keyboard. We argue the 4 E‘s model orientation revealing the fundamentally nature of the embodied musical mind. Ethical and practical possibilities for an enactive music cognition related to improvisation in the context of the skills and needs of 21st are suggested with the goal of helping DMIs designers and musicians to develop approaches based in possibility, imagination, and relationality, rather than in conformity to standardized practices and conventional music pedagogical purposes. Finally, we present some concrete cases of DMIs, and we describe how the experience of musical improvisation with them may be seen through the prism of such theories.